An Exploration of Political Polarisation and Coalition Governance in South African Local Government: Stability and Service Delivery Considerations - Makubalo, Xolisa; Rulashe, Tando; Gwala, Nosipho Nondumiso (UIN Sunan Gunung Djati Bandung, 2025)
As a result of the 2016 local government elections, South Africa's municipal system transformed profoundly. The system is shifting from a singular dominant party structure toward more complex and fragmented multiparty systems, which prioritise governance coalitions. Some observers celebrate this change as a move toward deeper democratisation, but many municipalities paint a different picture. The pursuit of inclusiveness and sharing responsibilities has brought about stagnation, strife, and inactivity in many coalition arrangements. This paper delineates some fundamental, persistent structural and behavioural difficulties using consociational theory and analysing policy documents alongside relevant academic literature. These are disputes among coalition partners, insufficient institutional structures to address conflicts, and ambiguous boundaries between the political sphere and administration. Collectively, there is an absence of political sophistication and an unwillingness to move beyond divisive politics and create effective governance. Such circumstances give rise to policy stasis, administrative paralysis, and interrupted public services. To ensure local democracy, this paper argues for more inter-party frameworks, targeted mediation frameworks, and an environment of unconditional goodwill to intra-party relations. Without such frameworks, rampant dysfunction may hinder coalition effectiveness. Furthermore, the paper’s findings reveal that there are destabilising effects of political polarisation on municipal governance, fragile coalitions and the absence of conflict management mechanisms, political infighting and administrative dysfunction, and undermined policy development and deteriorating service delivery affecting the implementation of service provision.